The determinants of financial distress among manufacturing company in Malaysia / Noreen Natasha Marhalim - Marhalim, Noreen Natasha (2018)
The objective of this study is to identify the determinants of financial distress in Malaysia manufacturing sector. The dependent variable of this study is time interest earned while the independent variables are debt to capital ratio and working capital. The type of data used in this study is panel data. The sample of study consists of 5 companies in the manufacturing sector and data collected over the period from 2008 until 2017. This study employs Pooled OLS in order to study the relationship between those variables. The result of this study shows that the debt to capital and working capital has a significant relationship with financial distress. In conclusion, it will be important determinants to use in to see the financial distress in the manufacturing industry.